Controlled synthesis of self-assembled 3D nanostructures using metastable atomic layer deposition. (December 2018) - Ziegler, M.; Yüksel, S.; Goerke, S.; Cialla-May, D.; Hübner, U.; Wang, D.; Schmidt, H.; Schaaf, P.
Abstract: An important feature of atomic layer deposition (ALD) is the fact that the coating that has been deposited is conformal to the substrate surface. Therefore, prepatterned substrates are usually used for the fabrication of 3D nanostructures using ALD. This article presents a new method to generate 3D silver-silica nanostructures using plasma-enhanced atomic layer deposition of silica with tri(dimethylamino)silane (TDMAS) and oxygen plasma as precursors. For this method, silver nanoparticles are used as templates, and during the deposition of silica, the repeatable process of the formation of metastable silver oxides and their decomposition is involved, leading to strong side reactions and the formation of 3D silver-silica hybrid nanostructures. This method is known as metastable atomic layer deposition (MS-ALD). Unlike the conventional ALD, the coating of MS-ALD is not conformal to the substrate surface. Rather, the 3D nanostructures are self-assembled because of side reactions. The geometry of the formed nanostructures can be easily adjusted by tuning the deposition parameters, such as dose time of both precursors and cycle numbers. In our study, we observed nanosponges with features sizes of up to 4 for less than 45 MS-ALD cycles. Nanowire-like silver-silica hybrid nanostructures are generated at higher cycle numbers with feature sizes of up to 10 μm. A similar trend could be observed for changing the dose time of both precursors of TDMAS and oxygen plasma. The height of the nanostructures increases with dose time of both precursors. In contrast to this trend, the surface coverage declines when the investigated parameters (number of cycles, TDMAS, and oxygen plasma dose time) are increased. Highlights: Metastable atomic layer deposition exploits substrate metastability to generate 3D nanostructures from 2D templates. 3D nanostructures are self-assembled due to strong side-reactions of the metastable substrate and the ALD precursors. Various silver-silica hybrid nanostructures can be generated by simply altering the MS-ALD process parameters. 3D nanostructure generation without the necessity of pre-patterned substrates.